Adjacent Local Binary Patterns Based on Color Space Fusion for Color Image Classification (Journal of Fiber Bioengineering and Informatics, 2015)
In this paper, we propose an improved image feature descriptor based on Local Binary Pattern, which is\rcalled Adjacent Local Binary Patterns based on Color Space Fusion (ALBPCSF). The proposed method\rfuses color feature and spatial relations. ALBPCSF uses the channel values of RGB and HSV color spaces\rto calculate the color feature. Then the proposed method considers the spatial relations which will be\rcombined with the color feature. Finally, an image classification system framework based on ALBPCSF\ris given. In order to validate the performance, our method is compared with previous methods on Corel\r1000 and MIT Vision Texture datasets. The results show that our approach is superior than other\rmethods in color image classification.